SKIN DISEASE RELATED TO METABOLIC SYNDROME IN WOMEN: A SYSTEMATIC REVIEW - Jani Sari Dabukke, Yeyen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: The metabolic syndrome" (MetS) refers to a group of clinical conditions that include abdominal obesity, hypertension, insulin resistance, and cholesterol. There was evidence that MetS is associated with a number of cutaneous disorders. This study aimed to review the correlation between metabolic syndrome and skin disease systematically. Materials and methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded Results: Database search yielded 294 articles, which were systematically eliminated, leaving 6 relevant articles. Analyzed articles showed the association between diabetes mellitus and hidradenitis suppurativa. Conclusion: Studies found a close connection between several cutaneous illnesses and MetS. Individuals who exhibit these conditions, which are indicators of MetS, should be questioned and, if necessary, tested for the condition.